The Development of Independent Learning Through Brain Based Learning Assistance to Improve Grit and Mathematical Connection Ability - Setyoningrum, Andi; Sukestiyarno, YL; Nugroho, Sunyoto Eko (Journal of Primary Education, 2020)
Low ability of mathematical connections affected by the lack of independence of students. Alternatives that can be used is using independent learning through mentoring using module based Brain Based Learning with grit character. The purpose of the research was to describe the module based Brain Based Learning and advisory guide category valid, the independent learning with assistance which was effectively improve the ability of mathematical connections, and describe the mathematical connection capability in terms of grit. The development stage modules using the procedures of Borg & Gall. The research was conducted at SDN 1 Manggungsari with sixth grade students as an experimental class. The analysis of the data used was the normality test, completeness, regression testing and test Gain. The results showed that Modules and advisory guide category was valid with the same score of 4.1; Self-regulated learning with assistance was effectively improve the mathematical connection, there is an increase of 0.53 at medium category, and 62.2% gave a positive response; Overall, student with high grit was able to understand the mathematical connection capability indicator. It can be concluded that self-assisted learning modules based Brain Based Learning with grit character can enhance the ability of the mathematical connections.